2014
DOI: 10.1007/s11999-014-3586-x
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Collections in Amputations Are Not Indicative or Predictive of Infection

Abstract: Background In the acute postoperative period, fluid collections are common in lower extremity amputations. Whether these fluid collections increase the risk of infection is unknown. Questions/purposes The purposes of this study were to determine (1) the percentage of patients who develop postoperative fluid collections in posttraumatic amputations and the natural course of the collection; (2) whether patients who develop these collections are at increased risk for infection; and to ask (3) are there objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
1
2
0
2
Order By: Relevance
“…This is consistent with our previously reported findings, that despite different injury mechanisms, biologic responses are similar in military and civilian extremity injury patients. [ 7 ] Furthermore, in larger cohorts of related studies[ 3 ], similar rates of dehiscence are observed, which speaks to the generalizability of our findings. In the larger military patient cohort, the mean wound dehiscence rate was 13% less than presented in this study; our inflated wound dehiscence rate for military patients in this study can be attributed to sample size–the larger study includes 116 wounds while our study includes 30 wounds.…”
Section: Discussionsupporting
confidence: 84%
“…This is consistent with our previously reported findings, that despite different injury mechanisms, biologic responses are similar in military and civilian extremity injury patients. [ 7 ] Furthermore, in larger cohorts of related studies[ 3 ], similar rates of dehiscence are observed, which speaks to the generalizability of our findings. In the larger military patient cohort, the mean wound dehiscence rate was 13% less than presented in this study; our inflated wound dehiscence rate for military patients in this study can be attributed to sample size–the larger study includes 116 wounds while our study includes 30 wounds.…”
Section: Discussionsupporting
confidence: 84%
“…Study done by Wadhwani et al showed 43% of stump problems in lower limb amputees. 13 Similarly, Polfer et al 5 reported on 300 cases of major lower limb amputation as having a return to surgery rate of 23% due to early hematoma formation. All these complications prolong hospitalisation and delay functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Next, our primary outcome measure, deep infection, was assessed by the findings of intraoperative cultures that were taken during débridement or revision surgery; therefore, subclinical or superficial infection did not receive consideration in our study. The decision to return for reoperation was made by the primary surgeon in nearly all cases, and was based on a reliable clinical picture concerning for infection taking into account pain, wound drainage or overt dehiscence, erythema, systemic inflammatory response, and elevated inflammatory markers [19]. The use of positive cultures as a component of the endpoint prevents this outcome measure from being unduly biased by false-positive indications for reoperation.…”
Section: Discussionmentioning
confidence: 99%